Proximate Composition, Mineral Profile and Trypsin-Inhibitory Activity of West African Leafy Vegetables: Influence of Urea Micro-Dosing and Harvest Time - Modoukpè Imayath Djibril Moussa; Adeola M. Alashi; Carole N. Sossa-Vihotogbé; Pierre B. Akponikpè; Mohamed N. Baco; André J. Djènontin; Rotimi E. Aluko; Noël H. Akissoé (Polish Journal of Food and Nutrition Sciences)
In order to ensure the nutritional quality of leafy vegetables produced under intensive cultivation systems, the proximate composition, mineral profile, and trypsin-inhibitory activity of three priority West African vegetable species ( Amaranthus cruentus, Ocimum gratissimum , and Solanum macrocarpon ) produced with urea micro-doses (20, 40, and 60 kg/ha) were compared with control leaves raised without urea. Plants were harvested three consecutive times to determine effects on nutrient and trypsin-inhibitory activity. Proximate and mineral compositions were mainly species-dependent (p<0.05) though the 60 kg/ha urea dose produced the significantly (p<0.05) highest moisture content in leaves. Calcium, copper, iron, and zinc contents were significantly (p<0.05) influenced by harvest time and its interaction with vegetable species. Furthermore, trypsin inhibition was significantly (p<0.05) higher for the second and third leaf harvests, which suggests that initial wounding from the first harvest enhanced synthesis of the inhibitor protein molecules